PENGARUH FREKUENSI PENGGORENGAN TERHADAP PENINGKATAN PEROKSIDA MINYAK GORENG CURAH DAN FORTIFIKASI VITAMIN A - Siswanto, Wahyu; Mulasari, Surahma Asti (Universitas Ahmad Dahlan, 2015)
Background: Palm oil industry in Indonesia is divided into two there are cooking oil and branded cooking oil. Currently there are a variety of branded cooking oil advantages, one of which is the fortification of vitamin A. Based on previous research it is known that 90% of households do frying as much as 4-8 times per day. Cooking oil used repeatedly can oxidize (react with air) so increasing levels of peroxide. Consumption of cooking oil containing high peroxide can cause health problems such as gastrointestinal irritation, diarrhea, and cancer. This study aims to determine the effect of the increase in the frequency of frying peroxide on cooking oil and cooking oil fortification of vitamin A was used. Method: This was experimental research with quasy experimental design. The research object in this study was cooking oil and vitamin A fortification of cooking oil used to fry out. Peroxide measurements made on a grill to 0, 1, 2, 3,4 with three repetitions in each cooking oil. Result: On average the lowest peroxide contained in the zero frying process was equal to 5.27 Mek O2/Kg (cooking oil) and 0.83 Mek O2/Kg (vitamin A fortification of cooking oil) and continued to increase until the fourth frying at 18.86 Mek O2/Kg (cooking oil) and 17.48 Mek O2/Kg (vitamin A fortification of cooking oil). Cooking oil used repeatedly peroxide can affect the increase in cooking oil (P value 0.010) and vitamin A fortification of cooking oil (P value 0.012) and no differences peroxide between cooking oil and vitamin A fortification oil (p value 0.065). Conclusion: There were the influence of the frying process to the increased frequency of peroxide value on cooking oil. There were the effect of the increase in the frequency of peroxide value frying cooking oil fortification on vitamin A. There was no difference between the peroxide cooking oil and vitamin A fortification of cooking oil Keywords: Cooking oil, difference, fortification, peroxide value, frying